Enabling systems for intelligent manufacturing in industry 4.0 sensing, smart and sustainable systems for the design of S3 products, processes, manufacturing systems, and enterprises - Molina, Arturo; Ponce, Pedro; Miranda, Jhonattan; Cortés, Daniel
This book introduces the concept of sensing, smart and sustainable systems (S3 systems) to support the design and redesign of products, services, business and manufacturing processes, manufacturing systems, and enterprises. The concept of S3 systems theory is introduced and explained in detail to support designers and engineers in their development task. This approach is embraced in the implementation of emergent Information and communication technologies and artificial intelligence techniques. The text helps the reader to understand the relationship between intelligent manufacturing, S3 systems and Industry 4.0. It presents a review of current approaches to design and development of technology-based products. Finally, it enlarges on the sensing, smart and sustainable systems theory to give examples of S3 systems as case studies.